Knowledge and practices about protein supplement use amongst students of a medical college - Kuntal Bandyopadhyay; Sougat Ray; Shruti Vashisht; Gurpreet Singh Bhalla; Manbeer Singh Sarao (Journal of Marine Medical Society, 2019)
Background: Nutrition and sports go hand in hand. With the availability of a wide range of protein supplements in the market and a risk taking mindset of the young generation to achieve fast and presentable results to their appearance or performance, a thorough knowledge and the selection of the right product becomes important. Materials and Methods: A descriptive cross-sectional study was conducted in a medical college in an urban locality over a period of 06 months. Participants were selected from a medical college by simple random sampling method and a total of 385 selected participants were distributed pre-tested questionnaires. Data was collected and the results were tabulated using appropriate statistics. Results: Amongst 385 participants (276 male & 109 females), 80 (20.8%) participants used supplements regularly. The mean age and BMI of protein supplement consumers was found to be 20.8 ± 1.4 years & 21.61 ± 1.9 Kg/m2. The association of use of supplements was found to be highly significant amongst those playing more than one sport (p<0.001), playing daily (p<0.001) and working out in gym (p<0.001). While the most common reason participants cited for consumption of supplements was to augment their diet and build muscles (46.3%), the commonest source of their information was found to be internet (65.8%). Conclusion: There still exists a huge gap in the knowledge and practices on the use of supplements amongst the college students which needs to be bridged and thus, by highlighting gaps in nutritional knowledge, sport nutrition professionals may begin to address these gaps by educating sportsperson with a view toward minimizing injury and enhancing sport performance.